Thermal Diffusivity and Quality Deterioration Index of Malaysian Pangasius Sutchi During Cold Storage - Abbas, Kassim Ali (2005)
The knowledge on thermal properties of food material to be preserved is considered as one of the basic requirements for conducting heat transfer studies and hence to design proper heat transfer equipments such as refrigerators, freezers and cold storages. The local designers obtain those thermophysical properties data from Europe and America (Ansari et al., 2002). Experimental measurements have been carried out for the specific heat, mass density, water content, thermal conductivity and thermal diffusivity of Malaysian freshwater Pangasius Sutchi fish during precooling process. The mass density was determined by measuring mass and volume of the fish samples and the water content was measured gravimetrically through drying of fish samples in oven. The remaining properties were calculated by empirical formula, which correlated these properties with water content of fish. The most significant part in the experimental work was designing and fabrication of an air blast cooling plant of constant 1 O C air stream temperature. This plant has played the vital role in minimizing the error of the used techniques as well as thermal diffusivity determination. A non-dimensionalized mathematical model of temperature variation with time and spatial coordinates was made and solved by finite difference method. Factors affecting the solution have been investigated thoroughly to deliver the most accurate and reliable results with the shortest computational time. The r,alculation procedure has been developed and proposed for heat transfer and simultaneous heat and mass transfer model. The proposed scheme showed more superior results when compared with the results reported in the literature and yielded consistently good agreements with the measurements. Three approaches of estimating the surface film conductance (h) during air-blast cooling process were developed by the present author. Based on the above mathematical model, a comparison between the developed and five of the existing literature approaches was made to identify the best one. A thorough investigation was conducted to establish the most suitable and reliable method of measuring the thermal diffusivity of Pangasius Sutchi out of important methods reported in the literature. Due to its superiority, Ansari's method was adapted to calculate the thermal diffusivity, through the transient temperature measurements at five known locations in the fish flesh and at the surface. The estimated h was used in this method to deliver reliable values of a. Four lots of fish samples were preserved in 4 chillers set at 0, 3, 5 and 10°C for 28 days according to normal practice. During the course of cold preservation, the which comprises overall acceptance (consumer acceptability acc). Secondly, chemical tests, which included the pH and Thiobarbituric acid (TBA) tests. These tests play the main role in determining the development of rancidity evolution in the fish under present investigations. ?he last type of test was the thermal diffusivity determination through transient temperature measurements across the muscles orientation, as well as along the n~uscleso rientation. The above study has revealed that the consumer acceptability (acc), pH and TBA value were found to be strongly dependent upon temperature and time of cold preservation. The results of acc and PH led to yield a graphical solution by which the consumer acceptability and the shelf life of the fish, during cold storage, could be predicted. TBA was correlated with thermal diffusivity ratio (a/a) to develop a tool by which rancidity of fish could be predicted without going through the chemical test, hence, a new quality deterioration index was developed. When the value of a 1a ,+sh= 1.0 indicates absolutely fresh sample, and a/a pex>, 1 . O the lesser the freshness.